A Swedish population-based study of complications due to acute rhinosinusitis in children 5–18 years old. (November 2021) - Hultman Dennison, S.; Hertting, Olof; Bennet, Rutger; Eriksson, Margareta; Holmström, Mats; Schollin Ask, Lina; Lindstrand, Ann; Dimitriou, Praxitelis; Stjärne, Pär; Granath, Anna
Abstract: Background: There are few population-based studies of complications due to acute rhinosinusitis in children. The aim was to clarify the admission and complication rate and analyze bacterial cultures in children five to 18 years old in Stockholm, Sweden. Methods: This was a population-based observational cohort study with retrospectively collected data from individual medical records, from 1 July 2003 to 30 June 2016 in Stockholm, Sweden. Hospital admissions of children with a discharge diagnosis of rhinosinusitis and related complications were reviewed. Results: Incidence of admission due to acute rhinosinusitis was 7.8 per 100 000 children per year (boys 9.2, girls 6.2) and 61% of the admitted children were boys. A severe – postseptal orbital, intracranial or osseous – complication, was present in 34% of admissions (postseptal orbital 28%, intracranial 6%, osseous 4%), resulting in an incidence of 2.6 severe complications per 100 000 children per year (boys 3.6, girls 1.6). Orbital preseptal cellulitis was present in 88% of admissions. Incidence of surgery was 1.3 per 100 000 per year (boys 1.8, girls 0.8) and the percentage of admitted children that had surgery increased with age. S. pyogenes was the most common pathogen found in the whole cohort (29 admissions), while S. milleri was the most common pathogen found among the children with severe complication and surgery. Conclusions: There is a relative high risk of severe complications in children between five to 18 years that are admitted due to acute rhinosinusitis. There is a need for prospective studies to further analyze the pathogens involved in complications due to acute rhinosinusitis.